V.2 - Rasure, K.A. (New Delhi, 2007)
Book Summary of Environment And Sustainable Development (3 Vols. Set) ? Environmentally Sustainable Development has been recognized as the right goal of economic development. Building sustainability has to be approached as a three fold task-social, economic and ecological, simultaneously. The "Sustainable Development" visualizes to restructure the traditional approach to development in a way that, the development activities are to be integrated with the environmental policies. The increasing population, lopsided developmental activities and rapid industrialization all over the world have caused ecological imbalances at local as well as global level. Thus sustainable development without environmental considerations is ruining the human life by deteriorating the life support system. Sustainable development aims at reconciling Man, Nature and Development for a better future. The main aim of almost all the Governments of the world is to achieve sustained and equitable development. But the growing environmental pollution in the world particularly in a developing economy like India, has created a number of obstacles to achieve the aim of sustainable development.
Keywords: Environment